Towards the Development of Structure‐Selective G‐Quadruplex‐Binding Indolo[3, 2‐b]quinolines. Issue 9 (25th January 2016) - Funke, Andrea; Dickerhoff, Jonathan; Weisz, Klaus
Abstract: The interaction of phenyl‐substituted indolo[3, 2‐ b ]quinolines with DNA G‐quadruplexes of different topology were studied by using a combination of spectroscopic and calorimetric methodologies. N5‐Methylated indoloquinoline derivatives ( Me PIQ) with an aminoalkyl side chain exhibit high affinities for the parallel‐stranded MYC quadruplex and a (3+1)‐hybrid structure combined with an excellent discrimination against the antiparallel thrombin‐binding aptamer (TBA) and the human telomeric (HT) quadruplexes. Dissociation constants for the binding of the ligand to the MYC quadruplex are in the submicromolar range, being below the corresponding dissociation constants for the antiparallel‐stranded quadruplexes by about one order of magnitude. Competition experiments with double‐helical DNA reveal the impact of indoloquinoline structural features on the selectivity for the parallel quadruplex relative to duplex DNA. Based on a calorimetric analysis binding to MYC is shown to be equally driven by favorable enthalpic and entropic contributions with no significant impact on the type of cation present. Abstract : Clear preference : Novel N‐methylated 11‐phenyl‐indolo[3, 2‐ b ]quinolines were tested for their binding to quadruplexes of different topology by a combination of spectroscopic and calorimetric methods. The ligands strongly discriminate between the various quadruplex structures, binding to the parallel quadruplex of the MYC promoter sequence with much higher affinity when compared to the antiparallel telomeric quadruplex (see figure).